Formation of the Research Thesaurus in Study of the Phenomenon of Dacha in Russian Literature of the 19th–21st Centuries - Olga A. Bogdanova (Studia Litterarum)
The article deals with the problems of studying the dacha as a special kind of artistic space in Russian literature of the 19th–21st centuries. The author of the article analyses dacha against the background of a much better studied “literary estate,” discusses and clarifies the concepts of “dacha culture,” “dacha text,” “dacha topos,” introduces into scientific circulation, shows relationship and dynamics of the terms “literary dacha,” “poetosphere of dacha,” “dacha myth.” The article lists main constitutive differences between the toposes of estate and dacha formed in the 19th and early 20th centuries. In Soviet time, due to the disappearance of the owner’s estate, a number of its functions (unity of nature and culture, storage of family and ancestral memory, etc.) passed to the dacha. Already since the 1920s, the “poetosphere of dacha” has been formed, largely due to the atmosphere of writers’ country villages (Tarusa, Peredelkino, Komarovo, etc.), which have become specific toposes of artistic creativity. In the 1960– 1980s — the period of mass dacha construction in the USSR — the “dacha culture” is enriched either by the romance of individual enterprise, or by the excitement of esoteric search. The literature of the turn of the 20th–21st centuries formed “dacha myth,” which has absorbed the antinomic connotations of the decentered worldview of modernity. For the purpose of scientific development of the phenomenon of literary dacha, the article sets the task of forming a research thesaurus as relevant to the subject of the study of the categories’ system.